Analysis Of Expressive Utterances Of Statuses UpdateOn Social Media Twitter Used By Students Of Muhammadiyah University Of Surakarta - Sari, Humaira; , Dra. Malikatul Laila, M. Hum; , Siti Zurhriah Ariatmi, M. Hum (2014)
This research aims to describe the linguistic form of expressive utterances and describe the intentions of expressive utterance in status updates on social media twitter used by students of Muharnmadiyah University of Surakarta The type of this research is descriptive qualitative research while the writer uses documentation and observation method as the method of collecting data. The data of this research are written utGrances made by students of English Deparftnent in Muharnmadiyah University of Surakarta. The result of the study shows that there are tbree kinds of expressive utterance from fiffy data found in status update on twitter. They are word, phrase (noun phrase and adjective phrase), and sentence (declarative, imperative, exclamatory). The word (2%), adjective phrase (4W, noun phrase Qo/o), declarative sentence (70yA, impertive sentence (14W, and exclamatory sentence (8"4. The types of expressive utterance found in status update on twitter dominated by declarative sentence. The intention of expressive uttrerance are (l2o/o) of yearning, (6%) of anger expression, $oA of welcoming, (8%) of congratnlating, (60/o) tiredness, (6%) of hoping, (8%) of happiness, (8%) of love, (6%) of thanking, (6%) sadness, (6%'1of sorrow, @%) of worrying, QVo\ of ttke, @YQ of dislike, Qo/o) of condolence, Q%) of condolence, (4%) of apologizing, Q%) of pleasure, (27o) of shock, and (2%) of longing. The intention of expressive utterance mostly appear in yearning. Total is (1007o) of expressive utterances.